I misunderstand you - Chakrapani, Rajnesh (Current Musicology, 2023)
This listening journal is about grief and family, the way sounds interweaves with text and realms of communication, how to ask for instructions to lay to rest the remains of the dead. An observer creates credibility for the doer, which in turn gives importance to the observer. The thread of the sound practice is trust. Who lets me hold space for them, who I let hold space for me. In recording this journey of Amma’s death, I thought a lot about how my practice with the listening journals influenced my speaking, my performance practice, my listening to people speak. I noticed that when I listen to my recording, I had a lot of umm’s, as if there was a hum in the middle of my speech, but it also created a hesitancy and pause to the authority of speech. Perhaps my listening practice is to create a habitat to experience, to move, to listen, to think.